2011
DOI: 10.1590/s1516-89132011000100023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sublethal concentrations of tobacco (Nicotiana tobaccum) leaf dust on some biochemical parameters of Hybrid catfish (Clarias gariepinus and Heterobranchus bidorsalis)

Abstract: The aim of this work was to study the effect of tobacco (Nicotiana tobaccum) leaf dust at sublethal concentrations (375.6, 187.8, 93.9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
(26 reference statements)
4
20
0
Order By: Relevance
“…Water quality parameters such as temperature, dissolved oxygen, free carbon (iv) oxide, pH, alkalinity and conductivity are important and affect fish health, growth and reproduction [43,44]. The characteristics of the oilfield wastewater used in this study have been evaluated by Akani and Gabriel [45]; the values agree with that of Wemedo et al [12], but differ from that of Obire and Amusan [2].…”
Section: Discussionmentioning
confidence: 60%
“…Water quality parameters such as temperature, dissolved oxygen, free carbon (iv) oxide, pH, alkalinity and conductivity are important and affect fish health, growth and reproduction [43,44]. The characteristics of the oilfield wastewater used in this study have been evaluated by Akani and Gabriel [45]; the values agree with that of Wemedo et al [12], but differ from that of Obire and Amusan [2].…”
Section: Discussionmentioning
confidence: 60%
“…Water quality parameters such as temperature, dissolved oxygen, free carbon (IV) oxide, pH, alkalinity and conductivity are important and affect fish health, growth and reproduction [14,28]. However, Richards [29] reported that the main cause of mortality in aquarium fish was the inadequate maintenance of the water environment.…”
Section: Discussionmentioning
confidence: 99%
“…Total protein is an important constituent of all the cells and tissues which play vital role in the physiology of living organism [14]. Since the fishes have little carbohydrate, protein is used to meet the increase in the energy demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain toxicants during the long-term influence on the organism of aquatic animals contribute to a decrease in the content of proteins [50][51][52][53], which negatively affects the synthesis of proteins [54]. Reduced protein content in the muscles is associated with the utilization of these compounds for the process of gluconeogenesis [55,56]. As the toxicity of the medium increases, the protein content in the tissues of hydrobionts decreases [57][58][59][60].…”
Section: Volume 70 the Effects Of Water Pollution On The Environmentmentioning
confidence: 99%